2009
DOI: 10.1074/jbc.m109.034140
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Interaction between Actuator and Nucleotide Binding Domains of Sarco(endo)plasmic Reticulum Ca2+-ATPase as Revealed by Single and Swap Mutational Analyses of Serine 186 and Glutamate 439

Abstract: Roles of hydrogen bonding interaction between Ser 186 of the actuator (A) domain and Glu 439 of nucleotide binding (N) domain seen in the structures of ADP-insensitive phosphorylated intermediate (E2P) of sarco(endo)plasmic reticulum Ca2؉ -ATPase were explored by their double alanine substitution S186A/E439A, swap substitution S186E/E439S, and each of these single substitutions. All the mutants except the swap mutant S186E/E439S showed markedly reduced Ca 2؉ -ATPase activity, and S186E/E439S restored completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
3
3
0
Order By: Relevance
“…6, 8, and 9), the Gln 202 side chain amide is within hydrogen bonding distance (ϳ3 Å) of the backbone carbonyl of Gly 626 , which is a critical residue at the catalytic site (15,44 186 and Glu 439 substantially increased the basal E2P dephosphorylation rate determined in the absence of ATP, and the swap mutation S186E/E439S almost restored the rate to a wild type-like level. These findings are in accordance with those of Liu et al (30), who from analysis of the E2⅐BeF crystal structures (9,45) pointed to a role for the hydrogen bond between Ser 186 and Glu 439 in stabilization of the interaction between domains A, N, and P in the E2P ground state. The pK a of the introduced glutamate in S186E was estimated to be extremely high, consistent with protonation and hydrogen bond formation between this glutamate and Glu 439 , thereby explaining the minimal effect of the mutation S186E (30).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…6, 8, and 9), the Gln 202 side chain amide is within hydrogen bonding distance (ϳ3 Å) of the backbone carbonyl of Gly 626 , which is a critical residue at the catalytic site (15,44 186 and Glu 439 substantially increased the basal E2P dephosphorylation rate determined in the absence of ATP, and the swap mutation S186E/E439S almost restored the rate to a wild type-like level. These findings are in accordance with those of Liu et al (30), who from analysis of the E2⅐BeF crystal structures (9,45) pointed to a role for the hydrogen bond between Ser 186 and Glu 439 in stabilization of the interaction between domains A, N, and P in the E2P ground state. The pK a of the introduced glutamate in S186E was estimated to be extremely high, consistent with protonation and hydrogen bond formation between this glutamate and Glu 439 , thereby explaining the minimal effect of the mutation S186E (30).…”
supporting
confidence: 82%
“…These findings are in accordance with those of Liu et al (30), who from analysis of the E2⅐BeF crystal structures (9,45) pointed to a role for the hydrogen bond between Ser 186 and Glu 439 in stabilization of the interaction between domains A, N, and P in the E2P ground state. The pK a of the introduced glutamate in S186E was estimated to be extremely high, consistent with protonation and hydrogen bond formation between this glutamate and Glu 439 , thereby explaining the minimal effect of the mutation S186E (30). Structural modeling suggested that in the swap mutant, serine and glutamate may still be able to interact by hydrogen bonding in the E2⅐BeF state, thus explaining the gain of function seen for S186E/E439S with respect to attaining a wild type-like basal E2P dephosphorylation rate.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Thereafter, the N-domain internal dynamics would serve to position and attain the linear conformation of ATP required for γ-phosphate transfer to the P-domain . Interestingly, molecular interaction of ATP in binding mode I is similar to that observed in Ca 2+ -ATPase in complex with the inhibitor thapsigargin and Mg 2+ in the absence of Ca 2+ (PDB entry 3AR4), except that the polyphosphate tail of ATP in a complex with Mg 2+ interacts with Glu439 on the opposite site. With regard to Ca 2+ -ATPase function, it has been reported that mutations Thr441Ala, Glu442Ala, Lys515Ala, Arg560Leu, Arg560Val, Arg560Glu, Cys561Ala, and Leu562Phe significantly decrease ATPase activity, the rate of phosphorylation, and the rate of Ca 2+ transport . Interestingly, Cys561Ala and Cys561Trp mutations decrease ATP binding affinity and generate only a slight decrease (∼20%) in the rate of Ca 2+ transport. , Cys561 also seems to be involved in protein stability as the recombinant N-domain Cys561Ala mutant shows a tendency to quickly precipitate …”
Section: Resultsmentioning
confidence: 85%
“…The most detailed study of inter-domain interaction was conducted on the Glu439-Ser186 contact; mutations of one or both residues were shown to affect the E1P to E2P transition [59, 60]. But the swap mutation (E439S/S186E) was found to retain normal behavior, clearly indicating the importance of this interaction.…”
Section: Discussionmentioning
confidence: 99%